THE INFLUENCE OF STRATEGIC COMPETENCE, ETHICAL COMPETENCE ON NETWORK COMPETENCE TO PREDICTE BUSINESS GROWTH - Arifin, Agnes Tasya; Utama, Louis (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to examine the effect of strategic competence, ethical competence on network competence and to examine the effect of strategic competence on business growth mediated by network competence. The population of this study is 100 SMEs in the field of clothing in Tanah Abang. The purposive sampling method was used by distributing online questionnaires, which were then processed using the smartPLS application. The results of this study are strategic competence, ethical competence has an influence on network competence. Strategic competence can also affect business growth mediated by network competence and ethical competence can also effect business growth mediated by network competence.